Challenges and Enablers for Smartphone Use by Persons With Vision Loss During the COVID-19 Pandemic: A Report of Two Case Studies - Senjam, Suraj Singh; Primo, Susan A. (Frontiers in Public Health, 2022)
Purpose Studies have reported that knowledge and skills to operate smartphones among people with profound visual loss are limited especially in low- to middle-income countries as many important functions of smartphones are unknown to them. This report presents smartphone use, its challenges, and enablers in two persons with profound visual impairment while executing their daily routine and instrumental living activities amidst the COVID-19 pandemic. Case selection and interview During the lockdown period, we provided tele (vision) rehabilitation service. From the list of the callers, we purposely selected two callers with significant visual impairment, one woman and one man, to allow us to gather rich information related to smartphone use, enablers, and challenges faced during the usage. A semistructured interview was done to obtain insights into the information. The selection criteria were (1) continuous smartphone use independently for more than 5 years; (2) graduation-level education or higher; and (3) no additional disabilities. Discussion We found substantial use of smartphones in executing their daily and instrumental daily living activities by these two participants. The extent of the use of mainstream apps for various tasks was almost equivalent to what we observed among sighted persons. The most important enabling factors were the presence of a screen reader “TalkBack” on Android phones and data connection of the mobile, followed by the ability to assess multiple languages using the text-to-speech feature. A supportive environment from peers or family members is important for the beginner. Poor battery backup, frequent unwanted ads or pop-ups while using the phone, not readable contents with a screen reader, e.g., CAPTCHA, and slow or unresponsiveness of the screen reader were frequent challenges faced by them. Both cases reported that around 80% of daily solutions were helped by using a smartphone. Conclusions The current advances in accessible technology of smartphones enable an individual with profound visual loss to use them almost equivalently as a sighted person. To reduce the gap in digital inclusion, people with visual impairment should be encouraged to use the smartphone for their daily solutions with attention to proper training.